Parenting Practices and Parenting Programs in Indonesia: A Literature Review and Current Evidence - Agnes Sumargi; Kate Sofronoff; Alina Morawska (ANIMA Indonesian Psychological Journal, 2014)
Research has indicated that parenting practices play an important role in the development of child emotional and behavioural problems. Despite its importance, there has been limited research that focuses on Indonesian parenting practices. Furthermore, with the increased prevalence of child emotional and behavioural problems, parenting interventions are needed. Research conducted in developed countries has found that parenting programs are effective in increasing parenting competence and reducing child emotional and behavioural problems. Unfortunately, evidence-based parenting programs are not yet available in Indonesia. This paper reviews the literature on parenting practices and parenting programs in Indonesia and proposes the Triple P-Positive Parenting Program as a promising intervention program for Indonesian families.